2014
DOI: 10.1002/2013jb010582
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneities around the megathrust zone of the 2011 Tohoku earthquake from tomographic inversion of onshore and offshore seismic observations

Abstract: We performed a three-dimensional seismic tomography around the coseismic slip area of the 2011 Tohoku earthquake. By combining data from the aftershock period collected by ocean bottom seismographs (OBSs), OBS data from previous studies off the Miyagi coast, and land seismic data, we modeled the detailed seismic velocity structure along the plate boundary from the Japan Trench to near the coastline. Our results indicate that V P , V S , and V P /V S along the plate boundary change drastically about 60 km landw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 59 publications
(112 reference statements)
2
17
0
Order By: Relevance
“…Cross sections (depth distribution) of faulting types across the large coseismic slip area off Miyagi Prefecture and north of the large coseismic slip area off Iwate Prefecture (rectangular areas, Figure b) show that normal faulting earthquakes in the offshore region were relocated at shallower depths than in the original catalogue (Figures d and f). This is consistent with depth determinations by sP depth phase [ Gamage et al , ] and temporal ocean bottom seismometer (OBS) data analyses for the earthquakes in the area [e.g., Hino et al , ; Obana et al , , ; Yamamoto et al , ]. We also found that most of the normal faulting events (green) in the horizontal range of 0–150 km are located in the upper plate after the Tohoku‐oki earthquake (Figures d and f).…”
Section: Resultssupporting
confidence: 90%
“…Cross sections (depth distribution) of faulting types across the large coseismic slip area off Miyagi Prefecture and north of the large coseismic slip area off Iwate Prefecture (rectangular areas, Figure b) show that normal faulting earthquakes in the offshore region were relocated at shallower depths than in the original catalogue (Figures d and f). This is consistent with depth determinations by sP depth phase [ Gamage et al , ] and temporal ocean bottom seismometer (OBS) data analyses for the earthquakes in the area [e.g., Hino et al , ; Obana et al , , ; Yamamoto et al , ]. We also found that most of the normal faulting events (green) in the horizontal range of 0–150 km are located in the upper plate after the Tohoku‐oki earthquake (Figures d and f).…”
Section: Resultssupporting
confidence: 90%
“…Smaller stars show hypocenters of the M 7.3 foreshock and M>7 aftershocks that occurred just after the mainshock earthquake above the large slip area. However, the result from Zhao et al [41] cannot be confirmed from the tomographic image obtained using data from this network [45]. This is because the spatial extent of the OBS network was too small for confirmation; only the southern asperity patch was covered by the network.…”
Section: Discussionmentioning
confidence: 77%
“…5h). Studies of seismic tomography do not support V P /V S ratios corresponding to such a high Poisson's ratio except in the toe part of the overriding plate (Matsubara and Obara 2011;Yamamoto et al 2014).…”
Section: Discussionmentioning
confidence: 94%